(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Upper lip deformities represent one of the most challenging problems in reconstructive and aesthetic facial surgery. The upper lip plays a central role in speech, facial expression, and perioral aesthetics, and its restoration requires precise anatomical, functional, and aesthetic reconstruction. This review discusses the anatomical background, classification of deformities, and modern surgical techniques used in the reconstruction of the upper lip, including local, regional, and free flap approaches. Recent advances in microsurgical reconstruction, fat grafting, and digital planning are highlighted, alongside considerations for aesthetic refinement and long-term rehabilitation.